Two cases of priapism associated with Quetiapine - Özge Şahmelikoğlu Onur; Hatice Kızılkale; Hüseyin Yumrukçal; Meltem Gürü (Psychiatry and Clinical Psychopharmacology, 2018)
Priapism is a painful, prolonged erection that occurs without any sexual stimulation. It is an emergency that may lead impotence, urinary retention, and gangrene as long-term devastating consequences. Priapism is attributed to the blockage of alpha-1 adrenergic receptors in the corpus cavernosum and associated with the use of typical antipsychotics, notably, thioridazine. Atypical antipsychotics are increasingly being prescribed and not frequently considered to cause priapism. This side effect has been reported in patients taking ziprasidone, risperidone, clozapine, quetiapine, aripiprazole and olanzapine. The intensity of binding to alpha-1 adrenergic receptors varies among all antipsychotics; quetiapine has an intermediate affinity. Priapism may be an idiosyncratic reaction which is correlated neither with the dosage nor the duration of use of antipsychotic drug. Quetiapine has been implicated in causing priapism in a limited number of reports. A history of prolonged erections may be a possible predictor of priapism during the use of quetiapine. We report two cases of priapism associated with quetiapine and a brief review.